RETROFIT POST-COMBUSTION CO2 CAPTURE EVALUATION FOR COAL POWER PLANTS - Susilo, Henry
As one of the largest coal consumers in the world for electricity generation, Indonesia is facing the high greenhouse gas (GHG) emissions, especially carbon dioxide (CO2) gas produced from coal combustion activities. This issue has triggered the Indonesian government to develop a strategy for decarbonization. Post-Combustion Capture (PCC) using chemical absorption technology is one of the most mature technology in decarbonization. The construction of a new coal power plant equipped with PCC technology is not the best option. Apart from requiring a large amount of money, Indonesia has committed not to build a new coal power plant starting in 2023. One of the solution that can be offered is to retrofit the existing coal power plant. This research will examine the retrofit installation of PCC technology in coal-fired power plants. Simulations on Aspen HYSYS and Aspen Process Economic Analyzer were used to evaluate the CO2 capture using Shell-Cansolv solvent (MDEA+PZ) and CO2 compression processes. A total of 6 typical coal power plants with the variations in capacity (300 MW, 600 MW, 660 MW, and 1000 MW) and type of steam cycle (subcritical, supercritical and ultra-supercritical) are then scored based on the Levelized Cost of Electricity (LCoE), emission intensity before capture, energy penalty, and the existence of flue gas desulfurizer (FGD). Technically, CCS facility causes emission intensity drops to 0,12 tonne CO2/MWh – 0,24 tonne CO2/MWh and energy penalty by 30,46% - 48,07% of the powerplant capacity. CCS unit requires CAPEX of $231.12 - $558.27 million and OPEX of $33.66 - $83.89 million/year. As a result, the cost of the CCS led to an increase in LCoE towards ¢11.1/kWh - ¢22.3/kWh. Based on technical and economical evaluation, ultra-supercritical 1000 MW powerplant with existing seawater FGD will be prioritized for CCS retrofit. This research is expected to assist the government in determining the policy and direction of decarbonization in Indonesia, especially in the implementation of PCC on Indonesian coal power plant.